How to achieve high-quality participation in voluntary environmental regulation: Influencing factors and decision mechanism - Feng Pan; Yanni Xu; Lin Wang (PLoS ONE, 2025)
This paper aims to explore the influencing factors and their decision mechanism of high-quality participation in voluntary environmental regulation, so as to present an ideal situation of synergistic and effective promotion of voluntary environmental governance. For this purpose, a four-party evolutionary game model of “local governments, enterprises, certification institutions and consumers” is constructed under the framework of voluntary environmental regulation, the interaction laws and equilibrium strategies of the multi-subject behaviors are investigated, then numerical simulation and sensitivity analyses are carried out with the help of MATLAB 2023(a). It is found that: active promotion by local governments, legal certification by certification institutions and strong concern from consumers can all promote high-quality participation in voluntary environmental regulation. Among them, legal certification by certification institutions is the key factor, and consumers’ strong concern has the weakest effect. The environmental governance direction of “local government supervise certification institutions, certification institutions review enterprises” can be established by promoting legal certification. Subsidies increased by local governments will help enterprises choose the qualified application strategy more quickly; penalties by local governments and exposure by the media can help certification institutions choose the legal certification strategy faster. This paper will enrich the theoretical research of voluntary environmental regulation from the perspective of participation effectiveness, supplement the practical basis for the high-quality implementation of voluntary environmental regulation, create a new pattern of multiple co-governance, and consolidate the ecological foundation for high-quality development.